Adaptive Capital Budgeting Practices in Micro-Family Enterprises: Exploring Informal Financial Strategies - Arima, Ulfah; Windiani, Titik; Ramadhani, Mardiatul; Dafa, Muhammad; Rahmatul Husna, Mutia (Entrepreneurship and Small Business Research, 2023)
This study explores applying capital budgeting theory in a micro-scale, family-run enterprise founded by a student entrepreneur in Indonesia. This paper used a qualitative case study, the research investigates how core principles of capital budgeting are applied informally in a resource-constrained context. Data were gathered through semi-structured interviews and field observations, enabling the exploration of investment decision-making, financial planning, and family involvement. Findings show that although the business does not apply complex techniques like NPV or IRR, it employs intuitive and adaptive methods such as payback period estimation and cash flow tracking based on experience, informal communication, and shared family judgment. These practices are grounded in the owner's academic background and sustained by collaborative family roles. The study contributes to the literature by highlighting how capital budgeting can be contextualised in micro-enterprise settings and emphasises the role of educational exposure and social capital in replacing formal financial systems. The findings also suggest the potential for integrating simplified digital tools to improve decision quality without overwhelming micro-entrepreneurs. This paper provides educators, development agencies, and policymakers with insight into supporting financial literacy and investment capability in the informal sector.